Automation in banking (London : Institute of Bankers, 1965)
This volume, presenting a discussion of automation as it applies in banking, is a particularly valuable addition to the series.
Lectures delivered in the Library of The Institute of Bankers, November, 1965.
osa 12/03/2019
Loans
Keywords: Banks and banking